1982
DOI: 10.1093/jn/112.6.1162
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postnatal Undernutrition on Ketone Metabolism and Its Relation to Metabolic Changes in Brain and Liver of Rats

Abstract: The effects of undernutrition on ketone metabolism and its relation to brain growth in developing rats were studied. In the first series of experiments, undernutrition was induced by increasing the litterr size from 4 to 16 pups. Body weight of pups was inversely related to litter size. Increasing the litter size lowered brain weight by 6-16% and liver weight by 20-46%. The ratio of brain weight:body weight was greater by 16 to 39% in the larger litters. Increasing the litter size did not alter concentration o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
2

Year Published

1985
1985
1992
1992

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
1
2
2
Order By: Relevance
“…Mello et al [20], using an undernutrition model similar to ours, found a decrease in glycemia and insulinemia on the day of birth in rats submitted to a low-protein diet. In contrast to PascualLeone et al [17] and Yeh et al [18], we found a marked increase in liver glycogen levels in 7-and 10-day-old undernourished rats.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Mello et al [20], using an undernutrition model similar to ours, found a decrease in glycemia and insulinemia on the day of birth in rats submitted to a low-protein diet. In contrast to PascualLeone et al [17] and Yeh et al [18], we found a marked increase in liver glycogen levels in 7-and 10-day-old undernourished rats.…”
Section: Discussioncontrasting
confidence: 99%
“…The decreased glycemia in malnourished rats from 10 days of life and the increased ketonemia at 10 and 15 days of age corre spond to data reported by Escrivd et al [ 10] and by Pascual-Leone et al [17], but differ from those reported by Yeh et al [18], who found a decrease in both parameters in 14- Each value is the mean ± SEM for the number of animals indicated in parentheses. Total ketone bodies are given by sum of (5-hydroxybutyrate and acetoace tate.…”
Section: Discussionsupporting
confidence: 77%
“…2). These results differ from Yeh et al (1982), who found in 14-day-old underfed rats a decrease in both parameters and also differ from Swiatek et al (1979), who did not find alterations in glycemia. The model used for undernutrition by these authors were: an increase in the litter size together with a 40% reduction in maternal diet and an increase in the litter size, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Pre-and postnatal protein undernutrition produces a great number of metabolic and structural alterations in the suckling rat (Morgane, Miller, Kemper, Stern, Forbes, Hall, Bronzine, Kissane, Hawrylewicz and Resnick 1978;Yeh, Zee, Owen and Walker 1982;Perry, Gamallo and Bernard 1986;Gamallo, Perry, Trindade, Pereira and Bernard 1989). We have previously reported that maternal protein undernutrition leads to the appearance of hyperketonemia in the rat pup (Gamallo et al 1989).…”
Section: Introductionmentioning
confidence: 98%